Impact of gender on outcome after coronary artery bypass surgery - Ennker, I.; Albert, A.; Pietrowski, D.; Bauer, K.; Ennker, J.; Florath, Ines (2009)
Following recent studies concerning the increased risk of coronary artery bypass surgery for women, the impact of sex is still a controversial issue. Between 1996 and 2006, 9,527 men and 3,079 women underwent isolated coronary artery bypass in our institute. To adjust for dissimilarities in preoperative risk profiles, propensity score-based matching was applied. Before adjustment, clinical outcomes in terms of operative mortality, arrhythmias, intensive care unit stay, and maximum creatine kinase-MB levels were significantly different for men and women. After balancing the preoperative characteristics, including height, no significant differences in clinical outcomes were observed. However, there was decreased use of internal mammary artery, less total arterial revascularization, and increasing creatine kinase-MB levels with decreasing height. This study supports the theory that female sex per se does not increase operative risk, but shorter height, which is more common in women, affects the outcome, probably due to technical difficulties in shorter patients with smaller internal mammary arteries and coronary vessels. Thus women may especially benefit from sequential arterial grafting. © SAGE Publications 2009.